American ginseng with different processing methods ameliorate immunosuppression induced by cyclophosphamide in mice via the MAPK signaling pathways - Zhang, Yan-Ting; Tian, Wei; Lu, Yu-Shun; Li, Zhi-Man; Ren, Duo-Duo; Zhang, Yue; Sha, Ji-Yue; Huo, Xiao-Hui; Li, Shan-Shan; Sun, Yin-Shi (Frontiers in Immunology, 2023)
This study aimed to clarify the effects of two processed forms of American ginseng (Panax quinquefolius L.) on immunosuppression caused by cyclophosphamide (CTX) in mice. In the CTX-induced immunosuppressive model, mice were given either steamed American ginseng (American ginseng red, AGR) or raw American ginseng (American ginseng soft branch, AGS) by intragastric administration. Serum and spleen tissues were collected, and the pathological changes in mice spleens were observed by conventional HE staining. The expression levels of cytokines were detected by ELISA, and the apoptosis of splenic cells was determined by western blotting. The results showed that AGR and AGS could relieve CTX-induced immunosuppression through the enhanced immune organ index, improved cell-mediated immune response, increased serum levels of cytokines (TNF-α, IFN-γ, and IL-2) and immunoglobulins (IgG, IgA, and IgM), as well as macrophage activities including carbon clearance and phagocytic index. AGR and AGS downregulated the expression of BAX and elevated the expression of Bcl-2, p-P38, p-JNK, and p-ERK in the spleens of CTX-injected animals. Compared to AGS, AGR significantly improved the number of CD4+CD8-T lymphocytes, the spleen index, and serum levels of IgA, IgG, TNF-α, and IFN-γ. The expression of the ERK/MAPK pathway was markedly increased. These findings support the hypothesis that AGR and AGS are effective immunomodulatory agents capable of preventing immune system hypofunction. Future research may investigate the exact mechanism to rule out any unforeseen effects of AGR and AGS.